Should women with postcoital bleeding be referred for colposcopy? - Batish, Avni; Sathiyathasan, S (Nepal Journal of Obstetrics and Gynaecology, 2017)
Electronic searches of literature published between 1980 and 2014 were undertaken using MEDLINE, Embase, CINHAL, and the Cochrane Database of Systemic reviews. Search items included: post coital bleeding, colposcopy, cervical cancer. Postcoital bleeding remains a cardinal warning sign of lower genital tract cancer and it is important to remember that it can also occur in the absence of cancer. In the vast majority of cases, there will be no sinister pathological abnormality. The common causes are usually benign conditions such as cervical ectopy and benign cervical polyps. Only a small number of women with PCB will have invasive disease of the lower genital tract.